WHAT IS COMPUTER NUMERICAL CONTROL (CNC)? MEANING, FUNCTIONALITY, AND APPLICATIONS (American Journal of Technology and Applied Sciences, 2025)
Computer Numerical Control (CNC) technology revolutionizes manufacturing by automating machine operations with computer systems, eliminating the need for constant human involvement. This article explores the fundamentals of CNC, highlighting its ability to manage tool movements with unparalleled precision using G-code instructions. Key functionalities include operations such as milling, turning, laser cutting, and 3D printing, enabling the production of complex and high-precision components. Essential considerations like material selection, tool maintenance, and workflow optimization are discussed to ensure efficient operation. Applications span industries such as aerospace, automotive, and architecture, showcasing CNC's role in creating highly accurate, customizable, and scalable products.